Increasing Drought Sensitivity and Decline of Atlas Cedar (Cedrus atlantica) in the Moroccan Middle Atlas Forests (FORESTS, 2011)
An understanding of the interactions between climate change and forest structure on tree growth are needed for decision making in forest conservation and management. In this paper, we investigated the relative contribution of tree features and stand structure on Atlas cedar (Cedrus atlantica) radial growth in forests that have experienced heavy grazing and logging in the past. Dendrochronological methods were applied to quantify patterns in basal-area increment and drought sensitivity of Atlas cedar in the Middle Atlas, northern Morocco. We estimated the tree-to-tree competition intensity and quantified the structure in Atlas cedar stands with contrasting tree density, age, and decline symptoms. The relative contribution of tree age and size and stand structure to Atlas cedar growth decline was estimated by variance partitioning using partial-redundancy analyses. Recurrent drought events and temperature increases have been identified from local climate records since the 1970s. We detected consistent growth declines and increased drought sensitivity in Atlas cedar across all sites since the early 1980s. Specifically, we determined that previous growth rates and tree age were the strongest tree features, while Quercus rotundifolia basal area was the strongest stand structure measure related to Atlas cedar decline. As a result, we suggest that Atlas cedar forests that have experienced severe drought in combination with grazing and logging may be in the process of shifting dominance toward more drought-tolerant species such as Q. rotundifolia.

The cost of stress resistance: construction and maintenance costs of leaves and roots in two populations of Quercus ilex (Tree Physiology, 2008)
We tested whether growth and maintenance costs of plant organs vary with environmental stress. Quercus ilex L. seedlings from acorns collected from natural populations in the northern Iberian Peninsula and in a lower elevation and putatively less stressful habitat in the southern Iberian Peninsula were grown in pots under the same conditions. Growth and maintenance respiration were measured by CO2 exchange. Young leaves from 5-month-old seedlings of both populations had similar mean specific leaf areas, nitrogen and carbon concentrations and specific growth rates, and almost identical growth costs (1.26 g glucose g−1). Leaf maintenance cost was higher in northern than in the southern population (27.3 versus 22.4 mg glucose g−1 day−1, P < 0.01). In both populations, leaf maintenance cost decreased by 90% as leaves aged, but even in mature leaves, the maintenance cost was higher in the northern population than in the southern population (3.38 versus 2.53 mg glucose g−1 day−1, P < 0.01). The growth costs of fine roots < 1 mm in diameter were similar in the two populations (1.20 g glucose g−1), whereas fine root maintenance cost was higher in the northern population than in the southern population (9.86 versus 7.45 mg glucose g−1 day−1; P < 0.05). The results suggest that the cost of organ maintenance is related to the severity of environmental stress in the native habitat. Because the observed differences in both leaves and roots were constitutive, the two populations may be considered ecotypes.
10.1093/treephys/28.11.1721